Taxing Working Memory during Retrieval of Emotional Memories Does Not Reduce Memory Accessibility When Cued with Reminders - van Schie, Kevin; Engelhard, Iris M.; van den Hout, Marcel A. (Frontiers in Psychiatry, 2015)
Earlier studies have shown that when individuals recall an emotional memory while simultaneously doing a demanding dual-task (e.g., playing Tetris, mental arithmetic, making eye movements), this reduces self-reported vividness and emotionality of the memory. These effects have been found up to one week later, but have largely been confined to self-report ratings. This study examined whether this dual-tasking intervention reduces memory performance (i.e., accessibility of emotional memories). Undergraduates (N = 60) studied word-image pairs and rated the retrieved image on vividness and emotionality when cued with the word. Then they viewed the cues and recalled the images with or without making eye movements. Finally, they re-rated the images on vividness and emotionality. Additionally, fragments from images from all conditions were presented and participants identified which fragment was paired earlier with which cue. Findings showed no effect of the dual-task manipulation on self-reported ratings and latency responses. Cued recall may not have been sufficient to elicit specific and continuous target retrieval for memory blurring to occur. The study demonstrates boundaries to the effects of the "dual-tasking" procedure.